(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper analyzes and compares two notable anti-slavery poems – Sarah Wentworth Morton’s “The African Chief” and Lydia Huntley Sigourney’s “To the First Slave Ship” – written in the early American Republic (between the American Revolution and the Civil War). Within our analysis we show that both “The African Chief” and “To the First Slave Ship” can be interpreted through a three-layered metaphysical social hierarchy made up of God, white slave-holder, and black slave. In both poems the roles awarded to each of the members of the hierarchy are the same – the black slave appears as the earthly martyr, the white slave-owner as the earthly master, whereas God assumes the role of mankind’s righteous heavenly judge poised to redeem the unjustly dehumanized Negro. However, though following the same general pattern, the two poems differ in how they specifically depict each of the three members of the hierarchy. The differences between the two poems in their respective images of God, white master, and enslaved Negro lead us to conclude that “The African Chief” contains a stronger criticism of slavery. The paper ends in a subjective statement that Wentworth Morton’s poem, due to the more pronounced sentimentalization of its black protagonist, is more likeable than Huntley Sigourney’s.